2004
DOI: 10.2166/wst.2004.0517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate components on hydrogen fermentation of multiple substrates

Abstract: As is well known, carbohydrate is the most appropriate organic material for hydrogen fermentation, and its hydrogen yield is significantly larger than that of protein. The fermentation of protein began with hydrogen production followed by hydrogen consumption, which helps overall hydrogen recovery. Both carbohydrate and protein are basic components of organic material, and yet carbohydrate is known to be a better substrate than protein in terms of hydrogen yield during hydrogen fermentation. This study used mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The estimated kinetic parameters for different Clostridium species suggest that C. beijerinckii L9 possessed a kinetic advantage in competing glucose with the other three strains because of its highest q max G and relatively low K Glu values. The estimated biomass yield coefficients (Y ) were within the range of reported values for acid producing bacteria (0.239-0.68) [33][34][35][36][37], but were higher than that of ADM1 (0.083 mmol/mmol), probably due to the biomass yield contributed by peptone metabolism [29,38]. Using bioenergetic calculations according to McCarty [39] and assuming glucose as the sole substrate, a theoretical true yield of 0.278 mmol/mmol for acid producing bacteria was obtained and the value was comparable to the estimated values listed in Table 3.…”
Section: Mathematical Model Simulationsupporting
confidence: 58%
See 1 more Smart Citation
“…The estimated kinetic parameters for different Clostridium species suggest that C. beijerinckii L9 possessed a kinetic advantage in competing glucose with the other three strains because of its highest q max G and relatively low K Glu values. The estimated biomass yield coefficients (Y ) were within the range of reported values for acid producing bacteria (0.239-0.68) [33][34][35][36][37], but were higher than that of ADM1 (0.083 mmol/mmol), probably due to the biomass yield contributed by peptone metabolism [29,38]. Using bioenergetic calculations according to McCarty [39] and assuming glucose as the sole substrate, a theoretical true yield of 0.278 mmol/mmol for acid producing bacteria was obtained and the value was comparable to the estimated values listed in Table 3.…”
Section: Mathematical Model Simulationsupporting
confidence: 58%
“…Corresponding to VFA production, the medium pH decreased from 7.2 to a value between 4.6 and 5.0. Release of ammonia nitrogen was insignificant during the BHP test, indicating that peptone was primarily utilized for biosynthesis of biomass [28,29]. The patterns of BHP test results for C. acetobutylicum M121 and C. tyrobutyricumi FYa102 isolates were very similar to those observed for C. butyricum ATCC19398 and C. beijerinckii L9 as shown in Fig.…”
Section: Bhp Tests For C Acetobutylicum M121 C Butyricum Atcc19398mentioning
confidence: 70%
“…The electrons produced by oxidation of amino acids would be consumed by the reduction of others amino acids, thereby leading to few available electrons for the production of hydrogen via ferrodioxin and hydrogenase [24]. In other words, hydrogen may be produced and/or consumed during the anaerobic degradation of protein [18,25]. Additionally, initial pH is an important factor that influences hydrogen consumption in the anaerobic fermentation of protein.…”
Section: Hydrogen Fermentations Of Glucose and Protein At Neutral Inimentioning
confidence: 99%
“…In addition, the existence of protein in the substrate is important for biohydrogen production since it provides a nitrogen source that enhances the growth and activity of H 2 -producing bacteria [7]. Kim et al [8] indicated that adding sewage sludge to enrich protein enhances the H 2 production potential, and obtained a 111.2 ml H 2 /g VSS/h specific H 2 production rate with the codigestion of food waste and sewage sludge.…”
Section: Introductionmentioning
confidence: 99%